A Simulation Study of the Fundamental Vibrational Shifts of HCl Diluted in Ar, Kr, and Xe: Anharmonic Corrections Effects. (3rd October 2012) - Padilla, A.; Pérez, J.
Abstract : We have calculated the vibrational solvent shifts of the fundamental bands of HCl diluted in Ar, Kr, and Xe solutions at different thermodynamic conditions by means of the molecular dynamics technique and a model for the isotropic part of the interaction depending on the vibration. The theoretical vibrational shifts, which were compared with the available experimental data, have been determined by considering both, the usual linear Buckingham terms and the nonlinear anharmonic corrections, and the latter omitted in a previous work for the HCl in Ar and Kr. We have found that the Buckingham contributions dominate the solvent shifts of the fundamental bands of HCl in Ar, Kr, and Xe, although the anharmonic shifts' present significant greater values than those obtained previously for N2 diluted in liquid Ar and pure liquid N2, both at normal conditions. We have analyzed the solvent shifts influence of the linear and quadratic (in the vibrational coordinate) oscillator-bath interaction terms and also the Dunham intramolecular potential effects on the anharmonic contributions.